The principal's role in improving the quality: A concepts framework to developing school culture - Sumiran, Sumiran; Waston, Waston; Zamroni, Zamroni; Mahmudah, Fitri Nur (Frontiers in Education, 2022)
This study aims to explore the role of principals in school culture so as to produce an ideal conceptual framework for principals in improving school quality. The method used in this research is qualitative with a case study approach. The research was conducted in MAN 2, Sragen, and MAN 2, Boyolali, Indonesia. The data analysis procedure used is Miles and Huberman with four procedures. Data analysis was carried out with the help of ATLAS.ti software version 8. Validity was carried out using data triangulation. The results of this study illustrate that the principal's role in school culture to improve school quality consists of role sets, attitudes and actions, personality characteristics, and control. The recommendations from this study are meant for principals at primary and secondary levels to help them improve the quality of their schools and create certain characteristics that are unique and superior compared to other schools.